Adsorption of Albumin on Silica Surfaces Modified by Silver and Copper Nanoparticles. (17th June 2013) - Kumari, Prity; Majewski, Peter
Abstract : Silver and copper nanoparticles, respectively, were produced on glass slides via magnetron sputtering. The experiments show that with magnetron sputtering the size and concentration of the nanoparticles can be easily controlled via sputter time and plasma power. Silver nanoparticles grow much faster than copper nanoparticles, which also require higher plasma power for their synthesis. Exposed to albumin solution, the glass slides with silver nanoparticles clearly show a delay in albumin attachment compared to pure glass slides. Glass slides with copper nanoparticles show a slight attachment of albumin even after 3 h of exposure. However, the albumin concentration on the surface of the glass slides was much smaller compared to pure glass slides and did not increase within 24 h.